2021
DOI: 10.12688/wellcomeopenres.16293.3
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on public health interventions in the management of the COVID-19 pandemic in Thailand

Abstract: Background: Any government needs to react quickly to a pandemic and make decisions on healthcare interventions locally and internationally with little information regarding the perceptions of people and the reactions they may receive during the implementation of restrictions. Methods: We report an anonymous online survey in Thailand conducted in May 2020 to assess public perceptions of three interventions in the Thai context: isolation, quarantine and social distancing. A total of 1,020 participants, of whom 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The findings revealed that many participants frequently engaged in practices regarding the “new normal” guidelines, which was similar to previous findings ( 28 , 36 , 41 ). In addition, 95.5% of participants always wore masks when they went to public places.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The findings revealed that many participants frequently engaged in practices regarding the “new normal” guidelines, which was similar to previous findings ( 28 , 36 , 41 ). In addition, 95.5% of participants always wore masks when they went to public places.…”
Section: Discussionsupporting
confidence: 89%
“…The findings will be useful for developing health education programs and improving QOL. The findings revealed that approximately 16.6% of participants experienced job loss during COVID-19 curfew restrictions, which is a greater proportion than that reported in previous studies before travel restrictions and curfews were implemented (11.4%, from 21 April to 4 May 2020) ( 35 ) and during travel restrictions in May 2020 ( 36 ). The results indicated that monthly family income was decreased during travel restrictions and curfews among for 68.6% of people in Public Health Region 6, which was a similar proportion to that found in a previous study ( 36 ) and a greater proportion than that before curfew ( 35 ).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The modelled effectiveness of NPIs was based on data from their application in Thailand during the first wave, hand hygiene and masking, social distancing, work from home, school closure and travel ban (or border closure) were tracked and incorporated in the model [15] , [16] , [17] . Further details on this aspect of the model are available in Supplementary B.…”
Section: Methodsmentioning
confidence: 99%